Memahami Teks, Melahirkan Konteks: Menelisik Interpretasi Ideologis Jamaah Tabligh - Didi Junaedi (Qur'an and Hadith Academic Society, 2013)
The dialectical process between the Qur’an, Hadith and other religious texts with reality will produce a variety of interpretations. This diversity of interpretations within different kinds of approaches: theological, legal, mystical, social, political, economical as well as various other points, in turn will present a discourse in the domain of thought, as well as practical measures in social realities. In this article, the author analyzes the theological and legal interpretation of Jama‘ah Tabligh. He also discusses a number of concepts which was arisen from their readings of a number of verses in the Qur’an and Hadith.